A Study of Nontraditional Teacher Certification in the Midwest - Phyllis K. Adcock (Educational Considerations, 2002)
In the next 10 years, there will be a need to hire over two million teachers, due to increases in K-12 enrollment, retiring teachers, and attrition of new teachers.